Women teachers training and life histories in Equatorial Guinea. A prospective study towards 2020 - Soto Arango, Diana Elvira; Avoro Nguema, María Teresa; Ruiz Cabezas, Adiela; Medina Rivilla, Antonio (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2016)
This paper presents the results of the research conducted in Malabo, Equatorial Guinea on life histories of a group of women teachers. The main objective focused on teachers training and practices. Historical and social methods for educational research were used, and the technique applied was narrative inquiry. The content analysis was carried out with the Atlas ti software, along with triangulation guided by expert advice; close attention was given to events affecting teachers, its relevance and the process of sharing this issues in order to understand the numerous changes in teaching practices, the current training scenarios, and their perspectives on the future from a collective imaginary. The findings expose that the teachers, involved in this research, present various training actions from colonial times to the present day, which have had great impact on their professional and personal lives. Education projection is evidenced towards 2020 with the necessary openness of meeting and dialogue with emerging ideals and aspirations within contexts having various sociocultural issues, where the main needs lie in ethnic groups integration and cultural identities recovery. There is still a long way to go and it will be safeguarded by those women teachers who are called “mamá” by their charisma and teaching vocation.